2015
DOI: 10.1111/plb.12282
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of essential oils of Thymus vulgaris and Origanum vulgare on phytopathogenic strains isolated from soybean

Abstract: The aim of this work was to study the antimicrobial activity of essential oils obtained from Thymus vulgaris (thyme) and Origanum vulgare (oregano) on phytopathogenic Pseudomonas species isolated from soybean. Strains with characteristics of P. syringae were isolated from leaves of soybean plants with blight symptoms. Ten of these could be identified in Group Ia of LOPAT as P. syringae. Six of these were confirmed as P. syringae using 16S rRNA, indicating the presence of these phytopathogenic bacteria in east … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“… (‐): Not done; * a From Oliva et al . (); b provided by A. Collmer; c provided by S. Lindow; d provided by Y. Zhao; e provided by D. Studholmer; f provided by L. Gallarato. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… (‐): Not done; * a From Oliva et al . (); b provided by A. Collmer; c provided by S. Lindow; d provided by Y. Zhao; e provided by D. Studholmer; f provided by L. Gallarato. …”
Section: Resultsmentioning
confidence: 99%
“…Our group previously reported the inhibitory effect of T. vulgaris and O. vulgare essential oils on phytopathogenic P. syringae isolated from soybean fields (Oliva et al . ). Here, the antimicrobial activity of both oils on P. syringae strains and anti‐biofilm and anti‐phytotoxin effects are reported.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…who reported on the chemical composition, antimicrobial and antioxidant activities of five different Thymus vulgaris L. (Lamiaceae) essential oils, and Oliva et al . who investigated the antimicrobial activity of the essential oils of Thymus vulgaris and Origanum vulgare on the phytopathogenic strains isolated from soybean . On the other hand, only a component analysis research has been reported about thyme (linalool chemotype) …”
Section: Introductionmentioning
confidence: 99%